Pengaruh Pemberian Senyawa Taurin dan Ekstrak Daun Dewa Gynura segetum (Lour) Merr terhadap Eritrosit dan Leukosit Mencit (Mus musculus) yang Diinduksi Benzo[α]Piren - Marlinda, Henny; Linirin Widiastuti, Endang; Susanto, G. Nugroho; ', Sutyarso (Jurnal Natur Indonesia, 2016)
Blood cancer (leukemia) is a cancer that occurs due to malignancy of blood cells. Treatment of leukemia generally causes damage to normal cells. Therefore, it needs a drug that has the effect of repairing cell damage and the ability to boost immunity of normal such as taurine and Gynura leaves which are expected to have anticancer and antioxidant properties. The purpose of this study was to investigate the effect of taurine and dewa leaf extract on blood tissues induced by benzo [α] pyrene in vivo, by looking at changes in body weight, the number of red blood cells (erythrocytes), the total number and differentiation of white blood cells (leukocytes) in mice (Mus musculus). Data were analyzed by One Way ANOVA test followed by LSD at 5% significance level. The treatment groups were the group I was given 0.2 mL of corn oil (negative control), group II (given benzo [α] pyrene as a positive control, Group III (given taurine 7.8 mg/BW/day starting from day 1 to 15 before the induction of benzo [α] pyrene until the end of the study), Group IV was given benzo [α] pyrene, then were given taurine 7.8 mg/BW/day were given 2 times a day, as well as the V group was given benzo [α] pyrene, then given a dose of Gynura leaf extract 277.8 mg /BW/day. The results showed taurine and Gynura leaf extract were able to obstruct leukemia by increasing body weight, erythrocyte, leukocyte, and the number of leukocyte differentiation which becomes normal again. In conclusion taurine has better ability for therapoitic than Gynura leaf extact against blood cells induced by benzo[α]piren